2018
DOI: 10.3390/brainsci8090169
|View full text |Cite
|
Sign up to set email alerts
|

Early Influence of Musical Abilities and Working Memory on Speech Imitation Abilities: Study with Pre-School Children

Abstract: Musical aptitude and language talent are highly intertwined when it comes to phonetic language ability. Research on pre-school children’s musical abilities and foreign language abilities are rare but give further insights into the relationship between language and musical aptitude. We tested pre-school children’s abilities to imitate unknown languages, to remember strings of digits, to sing, to discriminate musical statements and their intrinsic (spontaneous) singing behavior (“singing-lovers versus singing ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
34
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 96 publications
(151 reference statements)
3
34
0
3
Order By: Relevance
“…Accordingly, they show that the top-down allocation of attention similarly modulated EEG markers of syntax processing in M&L, particularly at late processing stages associated with cognitive reanalysis and integration. Otherwise, Christiner and Reiterer [20] found that links between musical aptitude and phonetic language abilities in pre-school children (i.e., imitation of foreign speech) were mediated by domain-general working memory resources. While none of these studies denies auditory-perceptual connections between M&L, they remind us that what we have seen so far is perhaps only the tip of the iceberg, with more complex entwinements still to be discovered.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Accordingly, they show that the top-down allocation of attention similarly modulated EEG markers of syntax processing in M&L, particularly at late processing stages associated with cognitive reanalysis and integration. Otherwise, Christiner and Reiterer [20] found that links between musical aptitude and phonetic language abilities in pre-school children (i.e., imitation of foreign speech) were mediated by domain-general working memory resources. While none of these studies denies auditory-perceptual connections between M&L, they remind us that what we have seen so far is perhaps only the tip of the iceberg, with more complex entwinements still to be discovered.…”
mentioning
confidence: 97%
“…As we will see, the studies follow two burgeoning trends in M&L research: First, they focused on common auditory processing of temporal regularities [ 6 , 7 , 8 , 9 ] that are thought to promote higher-level linguistic functions [ 8 , 10 , 11 , 12 , 13 , 14 ], possibly via mechanisms of neuronal entrainment [ 15 ]. Second, they explored top-down modulations of common auditory processes [ 16 , 17 , 18 ] by domain-general cognitive [ 19 , 20 ] and motor functions in both perception and production [ 21 ]. These topics were addressed using a broad toolkit of well-designed behavioral and computational approaches combined with functional magnetic resonance imaging (fMRI), near-infrared spectroscopy (NIRS) or electroencephalography (EEG) in different cohorts of participants.…”
mentioning
confidence: 99%
“…Furthermore, evidence for a dose-response relationship between musical practice and working memory supports the view that training, rather than any predisposition, produces changes in working memory capacity (Bergman Nutley et al, 2014). However, associations between working memory capacity and measures of musical aptitude (Strait et al, 2011;Degé et al, 2015;Christiner and Reiterer, 2018;Ireland et al, 2018) suggest that training-related advantages are not independent of innate abilities. Thus the evidence presented here support the view that musical training and musical aptitude both contribute to working memory performance among children.…”
Section: Relationships Between Music Training and Working Memory In Cmentioning
confidence: 89%
“…Several authors have reported that development of working memory may serve as a mechanism for emergence of cognitive abilities and other developmental outcomes (see Kraus et al, 2012). For example, there are reports of associations between working memory performance, music training or aptitude, and developmental outcomes such as neural encoding of speech (Strait et al, 2011(Strait et al, , 2012Christiner and Reiterer, 2018;Ireland et al, 2018), as well as cognitive skills related to reading abilities (Banai and Ahissar, 2013;Degé et al, 2015).…”
Section: Relationships Between Music Training and Working Memory In Cmentioning
confidence: 99%
See 1 more Smart Citation